REQUIREMENTS PLANNING BASE TRANSCEIVER STATION (BTS) PLACEMENT AND OPTIMIZATION OF SHARED TELECOMMUNICATIONS TOWERS - Asyik Fauzi (Jurnal Penelitian dan Pengembangan Komunikasi dan Informatika, 2014)
A cell phone is no longer a necessity but has become a complete lifestyle. However, not least problems are posed, one is the establishment of cellular relay towers used to hold the Base Tranceiver Station (BTS). BTS is a major infrastructure support in telecommunications operations that require the availability of land, buildings and air space, so that if the establishment of tower is not controlled then it will have an impact on the balance-room layout and aesthetics of the surrounding area. This study aims toperformBTS demand planning and telecommunicationtowerssharing in capacity perspectiveandoptimizingthe placement oftower locationsusing genetic algorithmsby considering the existing towers and potential points of of spatial plans. For5 years later, Blitar totally need 754 BTS that are supported by 258 telecom-shared towers. Genetic Algorithm methods can be used to optimize the location of telecommunications towers. Keywords: Arrangement Of Tower, BTS, Capacity, Cell Planning, Genetic Algorithm, Spatial Plan.